PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI PERSEBARAN FLORA DAN FAUNA DI INDONESIA DI SMA NEGERI NOEBANA KECAMATAN NOEBANA KABUPATEN TIMOR TENGAH SELATAN - Tanggela, Anggi M; Hasan, Muhammad Husain; Sunimbar, Sunimbar (Universitas Nusa Cendana, 2023)
The purpose of this research to find out whether there is an effect of the project-based learning model on the learning outcomes of Geography students at SMA Negeri Noebana. This type ofquasi-experimental research with nonequivalent control group research design. The population of this study was all students of class XI IPS. Which consists of 2 classes total 46 students. The class XI IPS 1 student with a total of 23 people as the experimental class and students in class XI IPS 2 with a total of 23 people as the control class. The sampling technique used a saturate sampling technique. Data taken by test and documentation techniques. Data analyzed by Independen Sampel T-Test Previously the data were tested for normality, homogeneity test, and linearity test. The results showed that (1) there was an influence in the application of the project-based learning modelon student learning outcomes with the results of Independen Sampel T-Test analysis obtaining a significant value on the model item of 0.002 <0.05. (2) Student learning outcomes have increased with the application of project-based learning models. (3) This is evidenced by the difference in the average learning outcomes of students who achieve KKM in learning with project-based learning which is 95% higher than the percentage of students who achieve KKM in learning withconventional models which only reaches 65%.